The Radiosensitivity of Haploid and Diploid Oedogonium Cardiacum and Studies on the Synchrony of Oedogonium Cardiacum - Johnson, Donald Kendall (My University, 1972)
The ɣ-radiosensitivity of haploid and diploid Oedogonium cardiacum cells was measured and compared to other cell lines. With the doubling of the chromosome complement, the Do value doubled, but the extrapolation number decreased four-fold. A general conclusion was drawn from the results that at all doses of ɣ-radiation, the diploids were more resistant than the haploids. A new radiation technique was used and compared to that used routinely in the laboratory. The further use of the technique was not recommended since the data obtained with the diploid line only was not as reliable as one would like.
The degree of synchrony of Oe. cardiacum zoospore cultures was measured using cell division as the biological end-point and a mathematical expression, the percent phasing, as the index of synchrony. It was intended that this research problem be secondary to the radiation studies. The percent phasing values were determined for cells growing in two inorganic media and in the presence of an inhibitor, hydroxyurea. However the degree of synchrony was not improved beyond that of the routine laboratory procedure. Attempts to improve the size of the synchronous populations collected also proved unsuccessful.
Keywords: radiosensitivity, haploid, diploid, synchrony, inhibitor, chromosome